1978
DOI: 10.1063/1.862295
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional magnetohydrodynamic turbulence in cylindrical geometry

Abstract: Ideal magnetohydrodynamic turbulence is treated using more realistic boundary conditions than rectangular periodic boundary conditions. The dynamical equations of incompressible magnetohydrodynamics and the associated fields are expanded in a set of vector eigenfunctions of the curl. The individual eigenfunctions represent force-free fields, but superpositions of them do not. Three integral invariants have simple quadratic expressions in the expansion coefficients: the total energy, the magnetic helicity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
4

Year Published

1984
1984
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(86 citation statements)
references
References 17 publications
3
79
0
4
Order By: Relevance
“…This has been hypothesized to be a direct consequence of the conservation of the three invariants of homogeneous incompressible MHD (total energy, magnetic helicity and cross helicity) in forced dissipative situations by Frisch et al (1975) and in selective decay situations by Montgomery et al (1978) and Matthaeus and Montgomery (1980).…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…This has been hypothesized to be a direct consequence of the conservation of the three invariants of homogeneous incompressible MHD (total energy, magnetic helicity and cross helicity) in forced dissipative situations by Frisch et al (1975) and in selective decay situations by Montgomery et al (1978) and Matthaeus and Montgomery (1980).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…At lower frequencies, the spectra apparently break to a flatter slope of -1. Although a slope of -1 is expected to characterize fully developed (isotropic) MHD turbulence at scales longer than the correlation length (Frisch et al, 1975;Montgomery et al, 1978;Matthaeus and Montgomery, 1981), it is unlikely that interplanetary turbulence is the origin of this feature in these spectra. One reason is that the Cl spectrum is not accompanied by a significant amount of magnetic helicity, nor is the helicity correlation length large.…”
Section: Spectral Analysismentioning
confidence: 99%
“…Taylor stated that provided a finite resistivity, magnetic reconnection approximately conserves global helicity and provides for the dissipation mechanism for reducing magnetic energy. [1,3] The selective decay hypothesis posits the energy selectively decays relative to magnetic helicity because the energy spectra peaks at higher wavenumbers, where dissipation is higher [4,5]. In the laboratory, experiments which rely on plasma relaxation are often confined with the help of flux conserving boundaries.…”
mentioning
confidence: 99%
“…Frisch et al [14] have suggested that threedimensional turbulent MHD flows can lead to an inverse cascade of magnetic helicity generating large scale magnetic structure. Montgomery et al [15] have discussed in detail the role of the ratio of helicity to energy, K/W, in the relaxation of turbulent flows.…”
Section: Relationship Between Helicity and Current Drivementioning
confidence: 99%